2019
DOI: 10.7554/elife.46134
|View full text |Cite
|
Sign up to set email alerts
|

Tailored tetravalent antibodies potently and specifically activate Wnt/Frizzled pathways in cells, organoids and mice

Abstract: Secreted Wnt proteins regulate development and adult tissue homeostasis by binding and activating cell-surface Frizzled receptors and co-receptors including LRP5/6. The hydrophobicity of Wnt proteins has complicated their purification and limited their use in basic research and as therapeutics. We describe modular tetravalent antibodies that can recruit Frizzled and LRP5/6 in a manner that phenocopies the activities of Wnts both in vitro and in vivo. The modular nature of these synthetic Frizzled and LRP5/6 Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 35 publications
3
99
0
Order By: Relevance
“…The relative position of two Fabs indicates the TM4s are likely at the dimer interface given the expected GPCR fold, consistent with the crystal structure of hFzd4TM ( Yang et al, 2018 ). Since Fzd appears to be monomeric on the surface of live cells, and hetero-trimerization of Wnt/Fzd with LRP6 is sufficient for activation of the intracellular β-catenin signaling ( Janda et al, 2017 ), the role of observed hFzd5 dimers in signaling remains unclear ( Tao et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative position of two Fabs indicates the TM4s are likely at the dimer interface given the expected GPCR fold, consistent with the crystal structure of hFzd4TM ( Yang et al, 2018 ). Since Fzd appears to be monomeric on the surface of live cells, and hetero-trimerization of Wnt/Fzd with LRP6 is sufficient for activation of the intracellular β-catenin signaling ( Janda et al, 2017 ), the role of observed hFzd5 dimers in signaling remains unclear ( Tao et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the preponderance of structural and mechanistic data point to a unique example of a heterodimerization-driven mechanism by a GPCR-like receptor Fzd and a Type-I receptor LRP5/6. This feature opens up the possibility of 'tuning' Wnt signaling through the use of alternative agonist molecules, such as antibodies and other dimeric scaffolds (Tao et al, 2019), to obtain a more granular understanding of Wnt biology and for developing regenerative therapeutics.…”
Section: Probing the Effect Of Structure-guided Hfzd5 Mutations On Simentioning
confidence: 99%
“…Interestingly, addition of RSPO1 increased F7L6 activity approximately 10-fold, but only augmented the activities of Wnt3a or FLAg F P+P -L 1+3 , a previously published WNT mimetic (Tao et al, 2019), by 2-fold (Figure 2 Supplement 1). A possible reason for this distinction is that F7L6 is selective for FZD7, whereas Wnt3a and FLAg F P+P -L 1+3 are capable of interacting with multiple FZDs.…”
Section: F7l6 Activates Wnt/β-catenin Signalingmentioning
confidence: 66%
“…Several other groups have described recombinant proteins similar in design to F7L6 and capable of heterodimerizing FZDs and LRP5/6(Chen et al 2020, Janda et al 2012, Miao et al 2020, Tao et al 2019). In contrast to these other WNT agonists that engage the CRD of FZD, the FZD7-binding arm of F7L6 binds the linker, or neck region, between the CRD and the first transmembrane domain of FZD7.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments using monomeric Wnt mimetics capable of binding only one FZD and one LRP6 demonstrated that 1:1 heterodimers are sufficient to initiate signaling (Miao et al 2020). Tetrameric ligands, such as F7L6 and those developed by others (Chen et al 2020, Tao et al 2019), may however augment and potentiate signaling by promoting receptor clustering. Additional experiments are needed to resolve the contribution of WNT versus DVL/AXIN to receptor oligomerization and signalosome formation.…”
Section: Discussionmentioning
confidence: 99%